1997
DOI: 10.1074/jbc.272.24.15459
|View full text |Cite
|
Sign up to set email alerts
|

Two Discrete Regions of Interleukin-2 (IL2) Receptor β Independently Mediate IL2 Activation of a PD98059/Rapamycin/Wortmannin-insensitive Stat5a/b Serine Kinase

Abstract: Many cytokines, hormones, and growth factors activate Janus kinases to tyrosine phosphorylate select members of the Stat transcription factors. For full transcriptional activation, Stat1 and Stat3 also require phosphorylation of a conserved serine residue within a mitogen-activated protein kinase phosphorylation consensus site. On the other hand, two recently identified and highly homologous Stat5a and Stat5b proteins lack this putative mitogen-activated protein kinase phosphorylation site. The present study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 50 publications
5
34
0
1
Order By: Relevance
“…Consistent with this hypothesis, a speci®c (Dudley et al, 1995;Dumont et al, 1998;Lu et al, 1998;Kirken et al, 1997), was found to induce erythroid di erentiation in dose-dependent manners not only in SKT6 cells but also in two other Friend leukemia-derived cell lines, TL200 and 1-2 (Figure 5a,b,c). In these experiments, growth-suppressing e ects of the drug became evident at the concentrations e ective in inducing di erentiation.…”
Section: Mek Inhibitor Pd98059 Induces Erythroid Differentiation In Smentioning
confidence: 54%
See 1 more Smart Citation
“…Consistent with this hypothesis, a speci®c (Dudley et al, 1995;Dumont et al, 1998;Lu et al, 1998;Kirken et al, 1997), was found to induce erythroid di erentiation in dose-dependent manners not only in SKT6 cells but also in two other Friend leukemia-derived cell lines, TL200 and 1-2 (Figure 5a,b,c). In these experiments, growth-suppressing e ects of the drug became evident at the concentrations e ective in inducing di erentiation.…”
Section: Mek Inhibitor Pd98059 Induces Erythroid Differentiation In Smentioning
confidence: 54%
“…On the other hand, wortmannin (Kimura et al, 1994;Damen et al, 1995;Kirken et al, 1997), an inhibitor of PI3K, did not induce di erentiation even at the concentrations that suppress cell growth to a comparable degree (Figure 5e), suggesting that growthsuppression alone was not su cient for inducing di erentiation. This ®nding also suggests that PI3K, a key component of another signaling pathway downstream of Ras, does not play a major role in the Rasmediated inhibition of erythroid di erentiation observed in this system.…”
Section: Mek Inhibitor Pd98059 Induces Erythroid Differentiation In Smentioning
confidence: 95%
“…Equal amounts of total protein from whole cell lysates were prepared and used for SDS-PAGE. For immunoprecipitation from clarified cell lysates, polyclonal rabbit antisera (2 ml/ml) specific to peptides corresponding to the unique COOH-termini of Stat5a or Stat5b (Kirken et al, 1997a), and rabbit polyclonal antibodies of ERa (H-184, Santa Cruz Biotechnology) or ERb (H-150, Santa Cruz Biotechnology) were used and captured after incubation with protein A-Sepharose beads (Pharmacia Biotech, Cat. # 17-0780-01).…”
Section: Solubilization Of Proteins Immunoprecipitation and Immunobmentioning
confidence: 99%
“…[114][115][116] Unlike other STAT proteins, STAT5a does not contain a classical MAPK recognition sequence, and is not phosphorylated by this kinase. Thus, the serine/threonine kinase, which phosphorylates STAT5a, remains unknown.…”
Section: Roles Of Serine Phosphorylation Of Stat Proteins In Leukemiamentioning
confidence: 99%